The Experiences of Young Liver Patients Transferring From Children's to Adult Services and Their Support Needs for a Successful Transition. (September 2018) - Toft, Alex; Taylor, Rachel; Claridge, Lee; Clowes, Charlotte; Ferguson, James; Hind, Jonathon; Jones, Rebecca; McClean, Patricia; McKiernan, Patrick; Samyn, Marianne; Coad, Jane
Background: The period of transition from pediatric to adult services represents a time when young people need support, information, and appropriate care in order to successfully move. It is a period that is associated with nonadherence and disengagement with care. Objective: To explore the experiences of young liver transplant recipients transitioning to adult services and determine what they require in order to achieve a successful move. The research also explored the possibility of using a mobile phone application (app) as a tool to support transition. Design: Qualitative approach using novel arts-based focus groups and one-to-one interviews. Participants: Twenty-one young people aged 16 to 25 years, 16 health-care professionals involved in their care, and 7 young people as follow-up. Participants used services provided by the 3 liver centers in England (Leeds, Birmingham, and London). Results: Data highlighted the variability of transition pathways in England for young people moving from child to adult health services. The results showed that they required clear information regarding transition processes including specific medical information and that there was a shortfall in such information. Support was required in the form of a designated transition coordinator or similar specialist who could act as a point of reference and guidance throughout the process. Transitions needed to be individualized and based upon transition readiness rather than age, although the research showed that age cut-offs were still used. Conclusion: Young people welcomed apps to provide information, reminders, contacts, and connections. Future research should explore the efficacy of such apps.